Pembuatan Video Iklan menggunakan Teknik Live Shoot dan Motion Graphic untuk Media Promosi di Instagram - Fersellia, Fersellia; Nugroho, Mei Aldi; Muflih, Ghufron Zaida; Fahmi Fachri, Fahmi Fachri (Jurnal Kridatama Sains dan Teknologi, 2024)
In the current digital era, promotion through visual media is the key to introducing products or business premises to the public. By using video as a promotional medium, companies can expand their marketing reach and make information more interesting and easy for consumers to understand. The problem faced by Kopi Sembilan is the lack of a creative and attractive promotional strategy, as well as not highlighting their Unique Selling Proposition (USP) in every product they promote. In comparison, their competitors were already using video to promote their products, giving them a significant competitive advantage. By studying the creative and technical aspects behind making advertising videos using live shoot and motion graphic technology, this research produced an advertising video that was rated very good by respondents, with a total percentage of 88.2%. This video was broadcast on Kopi Sembilan's official Instagram and received a positive response from the public. However, this research still has several shortcomings, such as the need to add creative elements such as 3D animation, improve animation smoothing, and add voice dubbing to increase the visual and audio appeal of advertisements. It is hoped that this suggestion can be taken into consideration for further development so that the promotion of Kopi Sembilan becomes better and more effective.